A history of western music - Grout, Donald Jay; Palisca, Claude V. (W.W. Norton & Company, 1996)
A History of Western Music has been recognized as the finest survey of Western art music since its first appearance in 1960. Setting the standard for all other music histories, this distinguished book has enlightened a multitude of students and connoisseurs with its thorough yet accessible overview of the field. Today's Grout/Palisca remains the most authoritative and useful text available, providing readers with insights into the music and its historical context. In preparing this Fifth Edition, Claude Palisca has applied the impeccable scholarship that made the book a classroom standard, while offering the most extensive revisions that the volume has yet seen. Page after page of the text has been rethought, rewritten, and newly conceived to bring it up to date and make it more readable, all without sacrificing Donald Grout's erudition and narrative flow. Twentieth-century developments now receive the same attention dedicated to other eras, with modern American music covered in a substantial new chapter of its own. The book has been enriched by discussions of works composed by women and of women's role in music history. All new terms and concepts are explained when they are introduced, and composers' dates are supplied when the composers are first named. A glossary makes finding brief definitions a simple task. A History of Western Music, Fifth Edition, features an engaging new design, with elements that visually enhance the text. Headings, subheading, and marginal headings provide a clear and consistent outline. Judicious touches of color highlight chronologies, diagrams, and technical discussions, and dozens of vignettes offer the wisdom of composers and critics in their own words. Sixteen full-color plates and numerous black-and-white images illustrate specific musical points and show music making in its social context. In all, no effort has been spared to bring to today's teachers and students the best Grout/Palisca ever.